Safety and Reliability – Safe Societies in a Changing World 2018
DOI: 10.1201/9781351174664-42
|View full text |Cite
|
Sign up to set email alerts
|

Human reliability analysis—accounting for human actions and external factors through the project life cycle

Abstract: Airplanes, ships, nuclear power plants and chemical production plants (including oil & gas facilities) are examples of industries that depend upon the interaction between operators and machines. Consequently, to assess the risks of those systems, not only the reliability of the technological components has to be accounted for, but also the 'human model'. For this reason, engineers have been working together with psychologists and sociologists to understand cognitive functions and how the organisational context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…For example, Azhdari [ 23 ] reached the conclusion that increasing the effectiveness of staff training and improving employee performance monitoring play a key role in reducing the incidence of human error events in the industry. Morais et al [ 27 ] introduced factors such as inadequate skills, lack of sufficient information, inadequate quality control, inadequate communication, inadequate working hours, design problems, and management issues as causes of human error. Amiri et al [ 10 ] also found that factors such as burnout and heat are considered as serious factors in the occurrence of accidents in construction industry projects.…”
Section: Discussion Of Survey Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Azhdari [ 23 ] reached the conclusion that increasing the effectiveness of staff training and improving employee performance monitoring play a key role in reducing the incidence of human error events in the industry. Morais et al [ 27 ] introduced factors such as inadequate skills, lack of sufficient information, inadequate quality control, inadequate communication, inadequate working hours, design problems, and management issues as causes of human error. Amiri et al [ 10 ] also found that factors such as burnout and heat are considered as serious factors in the occurrence of accidents in construction industry projects.…”
Section: Discussion Of Survey Resultsmentioning
confidence: 99%
“…Morais et al [ 27 ] studied the analysis of human reliability of human actions and external factors through the project life cycle. They cited factors such as inadequate skills, insufficient information, inadequate quality control, inadequate communication, inadequate working hours, design problems, management issues, social pressures, and inadequate task allocation as factors in human error.…”
Section: Research Backgroundmentioning
confidence: 99%
“…In this section we summarise the work carried out in Morais et al (2019a,b), Moura et al (2016) to estimate human error probabilities. We begin (Section 4.1) by recalling the MATA-D dataset built in Moura et al (2016) as well as the procedures carried out in Morais et al (2018) using Bayesian networks (Section 4.2) and in Morais et al (2019a,b) using credal networks (Section 4.3). Finally, we introduce our proposal in Section 4.4: the use of distortion models in order to overcome some of the shortcomings of the papers above.…”
Section: Estimation Of Human Error Probabilitiesmentioning
confidence: 99%
“…Following (Mkrtchyan et al, 2015), Morais et al constructed a Bayesian network summarising the interactions between the different factors (Morais et al, 2018). For this aim, each factor is represented by a node, and the arcs represent the significant conditional dependences between them, based on the analysis performed in Moura et al (2017a,b).…”
Section: Bayesian Network Approachmentioning
confidence: 99%
“…The influence of the human factor in the services sector is still dominant, and the efficiency of a service company as a whole critically depends on well-coordinated, motivated work of employees, and partner relations with each other, as well as attitude to their company. In turn, the organizational structure of the company, the attitude of management to employees, the schedule and workplace conditions, the nature of operations leave a serious imprint on the personnel functioning [3]. Today, many studies, methods and approaches are available devoted to analyzing the company business, optimizing the personnel work, improving the efficiency of business processes, which originate from F. Taylor's early 20th-century papers on the scientific organization of labor [4,5,6].…”
Section: Introductionmentioning
confidence: 99%